An experimental approach to archaeomorphometrics : with special reference to metapodials of artiodactyls in Sri Lanka - Rodrigo, Kalangi, (Access archaeology., 2022)
Measurements of bones and teeth play an important role in zooarchaeology. This study aims to publish a set of metapodial (Artiodactyl) measurements to facilitate comparisons with other bones from archaeological sites and to help the interpretation of measurement data; and to gain a better understanding of metric data.